2010
DOI: 10.1111/j.1472-8206.2009.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of quercetin, a polyphenolic compound, on mouse corpus cavernosum

Abstract: Flavonoids are plant-based phenolic compounds, and quercetin is the most abundant dietary member of this family. One of the most important characteristics of quercetin is its antioxidant property. The aim of this study was to investigate antioxidant effects of quercetin on corpora cavernosa of mice. Corpora cavernosa were isolated in organ baths, precontracted with phenylephrine (0.5 microm) and relaxant responses were mediated by acetylcholine (0.1-1 microm), electrical field stimulation (EFS, 1-16 Hz, 0.5 ms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…This finding is in line with what was observed by Ertug et al. [25] who found that quercetin restored exogenous NO responses when mice CC were exposed to free radicals. This could imply that a certain amount of oxidative stress is required in order for quercetin or resveratrol to exert their beneficial effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in line with what was observed by Ertug et al. [25] who found that quercetin restored exogenous NO responses when mice CC were exposed to free radicals. This could imply that a certain amount of oxidative stress is required in order for quercetin or resveratrol to exert their beneficial effect.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, neither resveratrol nor quercetin enhanced endogenously (Ach), exogenously (SNP), or neuronal (EFS) NO-mediated relaxation responses of CC. However, when oxidative stress was enhanced [25] who found that quercetin restored exogenous NO responses when mice CC were exposed to free radicals. This could imply that a certain amount of oxidative stress is required in order for quercetin or resveratrol to exert their beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, experiments on human CC and penile resistance arteries showed that antioxidant therapy ameliorates impaired NO‐mediated relaxations (both ACh and EFS) in diabetic patients with ED [26]. Oxidative stress alters NO‐mediated relaxations in mice CC, as the combination of the superoxide generator LY 83583 and the superoxide dismutase inhibitor DETCA inhibited corporal relaxations induced by EFS, ACh, and acidified sodium nitrite [14]. In our model of oxidative stress, we increased superoxide concentrations using the superoxide generator (free radical scavenger) hydroquinone [27,28] in combination with DETCA, an irreversible inhibitor of the Cu 2+ /Zn 2+ ‐containing superoxide dismutase [29].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, oxidative stress associated with hypertension [7], diabetes [8,9], aging [10,11], hypercholesterolemia [12], and radiation damage [13], can lead to ED. It was reported that oxidative stress impairs NO‐mediated relaxations of mice CC [14]. Hence, we were interested if oxidative stress also has an influence on the FAL‐/FAM‐induced corporal relaxations, as an impairment would limit their therapeutic relevance.…”
Section: Introductionmentioning
confidence: 99%
“…11 One could use lemon juice to prevent browning. The title of a report in the journal Fundamental & Clinical Pharmacology, "Protective effect of quercetin, a polyphenolic compound, on mouse corpus cavernosum," just about says it all.…”
Section: Antioxidants-caveatmentioning
confidence: 99%